Functional distribution of income: analysis of the divergence on the wage share between Germany and Spain 1999-2013 - Baratas, Luis (Papeles de Europa, 2016)
This paper presents an empirical approach to the evolution undergone by the functional distribution of income in the economies of Spain and Germany between 1999 and 2013. The striking fact about which we intend to shed light is the divergence in the evolution of the wage share that starts between the two countries since 2010. To do this, the work previously provides a literature review of the main contributions of authors from Political Economics approach have been identified as plausible determinants of the wage share. Once we have identified factors that determine the evolution of our dependent variable we proceed to contextualize them in the scenario where Spain and Germany are over period. Given the explanatory variables chosen and the empirical results, the main assumptions that sustains this work is that the reasons for the divergence in wage share are located in the weak productivity gains and the strong reduction of the average wage in Spain. In turn, we took the opportunity to aim some possible explanations for the divergence in wage shares (weak production structure and changes in collective bargaining, in part due to the launch of the euro).
Keywords: wage share; productivity; wages; unit labor costs; productive structure; and collective bargaining